Democratic Leadership and Its Role in Enhancing Community Participation in Village Development: A Case Study of Jatimulya Village, Majalengka - Setiawan, Amiruddin; Janah, Fitria Mar’atul (Journal of Multidisciplinary Research and Development, 2025)
The main problem of this research is that community participation in development is still not optimal, with low enthusiasm in planning deliberations and minimal contribution in implementation, this is thought to be caused by ineffective democratic leadership styles, lack of socialization and lack of acceptance of input from the community regarding this problem. Data collection in this research used field research with descriptive-quantitative analysis methods that describe and explain current social phenomena by examining the relationship and influence between Democratic leadership and Community Participation. This research method uses quantitative analysis techniques through simple linear regression analysis, product moment correlation coefficient and coefficient of determination which is intended to determine the magnitude of the influence of an organization's Democratic Leadership on Community Participation. The results of this research are based on hypothesis testing (t-test) which shows that there is an influence of Democratic Leadership on Community Participation of 79.7% and the remaining 20.3% is influenced by other factors. The conclusion in this research is that Democratic Leadership empirically has a significant influence on Community Participation in Jatimulya Village, Kasokandel District, Majalengka Regency.